Transparency in the Preparation of Terms of Reference in the Goods and Services Procurement System in BUMN - Wigianto Budiawan (Dinasti Research, 2024)
This research aims to identify factors that influence transparency in the preparation of TORs in the Goods and Services Procurement system in BUMN. This research uses a normative juridical method with a legal case approach that has permanent legal force. The research results show that the factors that influence transparency in preparing TORs are policies, regulations, technology and human resources that need to be perfected. Clear policies and adequate regulations can increase transparency, the use of technology can be used to simplify and speed up the procurement process and increase transparency in the procurement of goods and services. Human resources who have adequate competence and good morals are also very important to increase transparency in the procurement of goods and services. Based on the research results, the author recommends that BUMN strengthen policies and regulations related to the procurement of goods and services and increase the competence and morality of human resources involved in the procurement process. BUMN can utilize appropriate information technology to increase transparency in the procurement of goods and services. With these recommendations, it is hoped that BUMN can increase transparency in the procurement of goods and services.